2021
DOI: 10.1016/j.yhbeh.2021.105045
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory detection of trace amounts of plant volatiles is correlated with testosterone in a passerine bird

Abstract: In response to damage by insects, plants release herbivore-induced plant volatiles (HIPVs) into 17 the air. Insectivorous birds exploit these cues and, consequently, reduce the damages inflicted to the plants. However, little is known about whether they solely use HIPVs as foraging cues, or if 19 they also use them to modulate traits linked to reproduction. As caterpillars are the primary food 20 source required for insectivorous birds to raise offspring, their ability to locate and predict future 21 peaks in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 84 publications
0
21
2
Order By: Relevance
“…However, we have to admit that we do not know how exactly this dose mimics the situation when oak trees are infected by caterpillars. Furthermore, based on previous results with Quercus pubescens, where authors found that the emission of VOCs significantly increased from 42 hours after infestation (Graham et al unpublished data,in [29]), we decided to measure the volatiles of our trees after 62 hours from infestation or MeJA application. Therefore, it is possible that differences in the dosage as well as in the timing of the measurement may have provided different results in the analysis of volatiles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we have to admit that we do not know how exactly this dose mimics the situation when oak trees are infected by caterpillars. Furthermore, based on previous results with Quercus pubescens, where authors found that the emission of VOCs significantly increased from 42 hours after infestation (Graham et al unpublished data,in [29]), we decided to measure the volatiles of our trees after 62 hours from infestation or MeJA application. Therefore, it is possible that differences in the dosage as well as in the timing of the measurement may have provided different results in the analysis of volatiles.…”
Section: Discussionmentioning
confidence: 99%
“…after placing caterpillars on the sachets or applying MeJA treatment. We collected volatiles 62 hours after adding the treatments because previous results in another Quercus species, the downy oak tree (Quercus pubescens Willd) suggest that HIPVs significantly increase from 48 h after infestation by winter moth (Operophtera brumata) and green oak tortrix (Tortrix viridana) when compared to uninfested control trees (Graham et al unpublished data, in [29]). For each volatile measurement, we removed the organza bag from each branch and removed the caterpillars from the Herbivore-treated trees.…”
Section: Collection Of Plant Volatilesmentioning
confidence: 99%
See 1 more Smart Citation
“…We collected plant volatiles of all experimental trees ( n = 45), and four additional blank samples, 62 h (mean ± SE = 62 ± 1.05 h) after the beginning of the experiment, i.e., after placing caterpillars on the sachets or applying MeJA treatment. We collected volatiles 62 h after adding the treatments because previous results in another Quercus species, the downy oak tree ( Quercus pubescens Willd), suggest that HIPVs significantly increase from 48 h after infestation by winter moth ( Operophtera brumata ) and green oak tortrix ( Tortrix viridana ) when compared to uninfected control trees (Graham et al unpublished data, [ 29 ]). For each volatile measurement, we removed the organza bag from each branch and removed the caterpillars from the Herbivore-treated trees.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it seems that olfaction is used by birds to search for food [ 25 , 27 ], although the importance of vision and olfaction in the foraging behavior of birds is not completely understood yet [ 27 , 28 ]. Recent evidence shows that insectivorous birds can detect even small concentrations of HIPVs of herbivore-induced trees that are just developing new leaves [ 29 ], or small amounts of volatiles emitted during insect egg deposition [ 30 ]. Attraction to caterpillar-infested trees has been studied in different plant-insect-bird systems using ununified methodology [ 21 , 23 , 24 , 29 , 30 , 31 , 32 ] and often showing contradictory results.…”
Section: Introductionmentioning
confidence: 99%